RESPONSE OF MARIANNA PLUM HARDWOOD CUTTINGS TO BASAL WOUNDING AND DIPPING PERIOD IN IBA SOLUTION - ALI, ARI J.; MOHAMMED , RASUL R. AZIZ ARAM A.; . AHMAD, FARAYDWN K (Journal of Duhok University, 2020)
This research was conducted at the College of Agricultural Science Engineering/ University of Sulaimani/ Kurdistan region- Iraq, to study effect of wounding at the base of cuttings and different dipping periods (10s, 20s and 30s) in 2500 ppm IBA solution on hardwood cuttings of Marianna plum during 2018-2019. The experiment was designed in RCBD, and Duncun’s multiple ranges test (5%) was used for comparison of means. The studied parameters were rooting percentage, root number, root length, sprout bud number, shoot length and shoot diameter. Effect of individual factors revealed that wounding of basal end in hardwood cuttings gave no significant result for rooting percentage; wounded and unwounded cuttings gave %95.55 rooting. And also, quick dip of Marianna plum hardwood cuttings for different times (10, 20 and 30 seconds) in 2500 ppm IBA solution gave no significant result for any studied parameters; rooting reached 100% in cuttings dipped in 2500 ppm IBA for 20s. Interaction effects of the two factors showed no significant difference in rooting percentage. Rooting percentage reaches 100% in wounded and unwounded cuttings which were dipped in 2500 ppm IBA solution for 20s. The interaction effects on other root and shoot traits were not significant except in root length, the longest root (8.90 cm) found in cuttings were wounded and dipped in 2500 ppm IBA solution for 20s. Marianna plum is a species did not respond differently to basal wounding and quick dipping period in 2500 ppm IBA solution, as used for hardwood cuttings except in root length.